The representation of the Kalahari Thermal Low and its induced circulations over southern Africa in observations and models - Monyela, Bellinda Mashoene (Department of Oceanography, 2025)
Many studies investigated the impacts of different drivers on southern Africa's precipitation. But the influence of the Kalahari thermal low (KTL) on the southern Africa precipitation is overlooked and deserve more attention. In austral summer, the Botswana high and the Angola low are highly dependent to each other. Here, we reconcile these two most important features of the southern Africa's climate as part of the same robust atmospheric feature, the KTL. The KTL is the semi-permanent heating source in southern Africa that displaces poleward from its initiation in September until its maturation in January and recedes rapidly to disappear near where it originated in March. However, the relationship between the KTL and Angola low shows two distinct behaviours at different timescales. At seasonal timescale (annual cycle), the Angola low, driven by the KTL, responds as a thermal low. But at the interannual timescale, the reversal of the relationship suggests that the Angola low behaves as a tropical low and forms as a Gill-like response to the diabatic heating related to KTL. The KTL has a strong negative correlation with southern Africa precipitation. This teleconnection is explained by the leading mode of variability, but it is controlled more by the heat dome mechanism rather than by the advection of the mid-tropospheric dry air into the convective region. During the warm phase of KTL, the anomalous surface warming induces a tropospheric subsidence that develops later into a heat dome, conducive to drought. In the cold phase, the reduced mid-tropospheric divergence favours the development of an anomalous moisture flux convergence that triggers the deep convection and leads to more rainfall. Furthermore, the accurate representation of the Hadley circulations over southern Africa revealed the coexistence of both shallow and deep Hadley circulations over southern Africa. The deep mode is characterized by a strong convection that occurs over the tropical southern Africa (between 25o–15oS). The shallow mode is associated with the thermally-driven shallow meridional circulation (SMC) over subtropical southern Africa (between 35o–25oS) and formed by the divergent flow. Its upper branch is constituted by the mid-tropospheric northerly jet and the lower branch being formed by the low-level southerly jet. This vertical structure of the SMC has been mistaken by the observed opposite recirculation that is widely reported in the literature. This recirculation is dominated by the rotational wind, with its upper branch constituted by the subtropical southerly jet (STSJ) that connects the dry subtropical southern Africa to the wet tropical southern Africa. The SMC contributes substantially to the moisture budget, with limited supply from the mid-tropospheric circulation. However, the mid-tropospheric air is predominantly advected westward towards the Atlantic Ocean by the AEJ-S rather than northward into the convective region by the STSJ as argued in the literature. Current climate models from CMIP6 not only underestimate the intensity of the KTL and its spatial structure, but also fail to reproduce the physical mechanisms through which the KTL controls the regional moisture budget.